Furniture to promote healthy lifestyle at office / Abu Bakar Abdul Aziz - Abdul Aziz, Abu Bakar (2013)
Nowadays, issues on healthy lifestyle are very important and people need to give more attention and have awareness about health. Malaysians need to adopt a healthy lifestyle as a culture to enable them to be productive and continue to contribute to the family and country. Sedentary lifestyles are related with obesity and are a major risk factor for the metabolic syndrome or obesity. The Statistic of Malaysian overweight and obese is quite high. 30 percent of Malaysians are overweight while another 30 percent are obese. The recent studies showed that 3 out of 4 Malaysians do more mental work than physical work. This research is to enhance and improve the quality of life by adopting the healthy lifestyle and reduce the sedentary lifestyle at the office environment. It is important to encourage people and give awareness to adopt the healthy lifestyle at the workplace. The methodology used is qualitative, personal observation and peers review will be used. Target area for this research if office area and the population are office workers aged between 25 to 64 years old.Furniture is an important thing that always related with daily office workers activity and the researcher promotes a healthy lifestyle and reduces the sedentary lifestyle with designing exercise furniture that incorporates the physical exercise at the office. The researcher selected eight physical exercises which are punching, sparring, push ups, sit ups, dips, lunges, side flexion and thoracic spine. These exercises are combinations from three types of exercise which is aerobic, anaerobic and flexibility exercise. The furniture also can be used for relaxing and can seat three people. Many workers spend a majority of their waking hours at the workplace and the office is a suitable area that can to encourage a healthy lifestyle. Hence, the integrated furniture and physical exercise can encourage and give the awareness for people to move and make people healthier.